9 Levels for Value Systems - Operationalising and measuring the level resistances - Thomas Dobbelstein; Rainer Krumm (Journal of Applied Leadership and Management, 2016)
How can personal resistances to values within the meaning of the 9 Levels for value systems be reliably measured?
Keywords: 650; 9 Levels; Value System